An extension of Horn's theorem for a space of locally integrable functions - Hernan R. Henriquez; Eduardo A. Hernandez (International Journal of Mathematics and Mathematical Sciences)
In this paper we extend the fixed point theorem of Horn's to the space of locally integrable functions from (−∞,0] into a Banach space X.